REVEALING CULTURAL EXCLUSIVISM IN BALI THROUGH WASTRA BEBALI - Tjok Istri Ratna C. Sudharsana (UPT Pusat Penerbitan LP2MPP ISI Bali, 2021)
The unpopularity of wastra bebali among the Balinese themselves inspired the writer to explore further and in depth about the thoughts of the sulinggih (pedanda) who intensely described Balinese Hindu religious teachings through the visual art in the medium of textile called wastra bebali, as well as what made it not so popular. known even by the people themselves. Case study research and cultural studies approach is used to uncover the causes of the unpopularity of wastra bebali in Balinese society. The results of the study indicate that there is an indication of the exclusivity of the geriya as the upstream of the knowledge and practice of making wastra bebali as the key factors in the unpopularity of wastra bebali, the exclusivity of the geriya occurs as a result of several accumulative factors caused by past experiences. This attitude of exclusivity is like a double-edged sword, an attitude that can protect the existence of wastra bebali while making it slowly extinct. The emergence of figures like a descendant of the Brahmins who consciously began to introduce wastra bebali to the community, needed support from local researchers, so that they could bring this wastra bebali as an exclusive product not only for the geriya but for Balinese society. Keywords: Wastra Bebali, Cultural Exclusivism, Bali